Awareness and Knowledge of the Surgical Safety Checklist among Healthcare Professionals in University Teaching Hospital, Kathmandu, Nepal - Uprety, A.; Kobashi, Y.; Ozaki, A.; Shrestha, D.; Ghimire, B.; Sedain, G.; Sigdel, S.; Higuchi, A.; Tsubokura, M.; Singh, Y. P. (Kathmandu University Medical Journal, 2021)
Background An introduction of the World Health Organization Surgical Safety Checklist (WHO SSC) is essential to promote surgical safety. Objective To obtain country-specific information regarding the checklist in a leading medical institution in Nepal. Method The present research was a cross-sectional study with a survey conducted among healthcare professionals working in the operation theatre at the Tribhuvan University Teaching Hospital (TUTH) in Kathmandu, Nepal. A questionnaire was distributed to 150 healthcare professionals working in the operating theatre. Responses to the questionnaire were analysed descriptively and regression analyses used to identify factors associated with awareness of the checklist. Result In total, 127 healthcare professionals participated in the study, of whom 118 (92.9%) had been aware of the WHO SSC. A substantial proportion of participants (108, 91.5%) were not satisfied with the prevailing practice whereby the checklist was not routinely used during surgery. Lack of appropriate training was the most prevalent barrier to the checklist use (72, 67.9%), followed by unwillingness of staff to use the checklist (54, 50.9%), and lack of experience (42, 39.7%). The mean score on the survey was 6.0 out of 10. Regarding the results of the regression model on survey scores, surgeons had higher scores compared to nurses (unadjusted coefficient 0.80, 95% CI 0.20-1.40). Conclusion Most of the healthcare professionals were aware of the WHO SSC, however multiple barriers to the checklist use were identified. It is important to establish an effective use of WHO SSC in the operation theatre.